2011
DOI: 10.4992/jjpsy.82.158
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between grandparent role and subjective well-being of young-olds

Abstract: This study explores the influence of self-processes involving grandparenthood on the frequency of contact with grandchildren and grandparent satisfaction, and the influence of these self-processes, frequency of contact, and grandparent satisfaction on subjective well-being. A mail survey was conducted with randomly selected people between 65-74 years of age (N = 226) living in a city. The results showed that grandparent centrality and grandparent identity meanings influenced the frequency of contact with grand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Koyano, Shibata, Haga, and Suyama (1989) developed a scale to measure various components of subjective well-being and came up with the Life Satisfaction Index K or LSIK. Because the LSIK has been widely used in Japanese aging studies (e.g., Nakahara, 2011a;Okamoto, 2008b), for this study, subjective well-being is assessed using LSIK.…”
Section: Subjective Well-being and Agingmentioning
confidence: 99%
“…Koyano, Shibata, Haga, and Suyama (1989) developed a scale to measure various components of subjective well-being and came up with the Life Satisfaction Index K or LSIK. Because the LSIK has been widely used in Japanese aging studies (e.g., Nakahara, 2011a;Okamoto, 2008b), for this study, subjective well-being is assessed using LSIK.…”
Section: Subjective Well-being and Agingmentioning
confidence: 99%
“…Moreover, previous studies have verified the relationship between family interactions and identity meaning within a family ( Reitzes and Mutran, 2006 ; Nakahara, 2011 ; Heintzelman and Bacon, 2015 ). Reitzes and Mutran (2004) demonstrated that positive identity meaning is related to subjective well-being, as also reported in a Japanese sample by Nakahara (2011) and Nakahara et al (2012) . Relying on support from others can diminish sense of competence in older adults ( Siebert et al, 1999 ), and associated feelings of neediness and dependency can disturb identity meaning.…”
Section: Introductionmentioning
confidence: 77%
“…Indeed, such interactions are not likely to undergo a short-term transformation. However, older adults with grandchildren may show different patterns ( Reitzes and Mutran, 2004 ; Nakahara, 2011 ; Nakahara et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%